A collagen matrix biomembrane preparation method, collagen matrix biomembrane and application thereof
Patent Information
- Application Number
- CN202410101462.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-24
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2044-01-24
AI Technical Summary
[0013]有鉴于此,本申请的目的在于提供一种胶原基质生物膜制备方法、胶原基质生物膜及其应用,以解决现有技术中存在的软组织增量生物替代材料体积稳定性差,力学强度差,材料易变性,难以与患者伤处充分匹配的缺点
[0046]本发明提供的一种胶原基质生物膜通过选用天然来源动物组织为原料制备脱细胞基质,再通过对脱细胞基质进一步加工,获得具有致密层和疏松海绵层双层结构的胶原基质生物膜。
Smart Images

Figure CN117919511B_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of biomaterials technology, and in particular to a method for preparing collagen matrix biomembranes, collagen matrix biomembranes and their applications. Background Technology
[0002] The most common treatment for insufficient periodontal soft tissue is periodontal soft tissue augmentation surgery. However, the soft tissue required for this surgery often comes from autologous free gingival flaps / connective tissue flaps, which has limited availability, causes significant postoperative patient reactions, and restricts the surgical area. Therefore, research and development of soft tissue substitute materials remains a hot topic.
[0003] Among existing technologies, acellular dermal matrix (ADM), represented by AlloDerm and mucoderm, and xenogeneic collagen matrix (XCM), represented by Mucograft, are the most representative soft tissue replacement materials. Although evidence shows that ADM is the closest transplantation alternative to connective tissue grafts (CTG), long-term follow-up results show that the treatment effect obtained using ADM has the disadvantage of poor gingival margin stability, which may be related to its lack of ability to induce epithelial cell keratinization. XCM has already been marketed in China, with the product name Mucograft. It has a two-layer structure: a dense structure with high strength that can be sutured and allows for wound protection in an open healing environment; and a second structure that is a porous collagen sponge formed by freeze-drying collagen fiber pulp, which helps stabilize blood clots. To avoid introducing additional cross-linking substances and ensure the product's biocompatibility, Mucograft adopts an uncross-linked design (EP1252903B1). From a biological perspective, similar to autologous connective tissue grafts, the purpose of XCM is to maintain space to facilitate the colonization of fibroblasts migrating from surrounding soft tissue. The matrix is then gradually absorbed and replaced by autologous soft tissue. Gingival cells in the oral connective tissue are subjected to complex mechanical forces during chewing, speech, tooth movement, and orthodontic treatment, especially during wound healing after surgery, which may generate internal and external forces that stress newly formed tissue. Therefore, the volumetric stability of the graft substitute is crucial, implying that cross-linking of the material is essential.
[0004] Analysis of Mucograft products revealed that its sponge layer is made from purified collagen fiber slurry through freeze-drying. Due to the lack of cross-linking, its biostability and mechanical properties are poor, especially after water absorption, where the inter-fiber bonding strength significantly decreases, leading to collapse under pressure. Therefore, it negatively impacts the stability of blood clots during complex oral movements. To address the limitations of Mucograft, researchers developed a second-generation material by adding cross-linking to the original product. This second-generation material features a thick, single-layer sponge structure and utilizes chemical cross-linking to achieve excellent volume stability (application number 201580067861.4). However, the single-layer sponge structure lacks the strength support of a dense layer, resulting in low suture strength that fails to meet clinical suturing requirements. Furthermore, the introduction of chemical cross-linking agents (such as glutaraldehyde, EDC, and EDC-NHS) reduces biocompatibility, negatively impacting soft tissue healing and hindering tissue integration.
[0005] As H. Mathes et al. pointed out in their article "A Bioreactor Test System to mimic the Biological and Mechanical Environment of Oral Soft Tissues and to Evaluate Substitutes for Connective Tissue Gafts", soft tissue augmentation products need to achieve a balance between mechanical stability (high cross-linking degree) and smooth soft tissue healing (low cross-linking degree) to obtain the best soft tissue repair effect.
[0006] The best way to reinforce adhesive raw materials is to introduce cross-linking structures, mainly divided into physical cross-linking and chemical cross-linking. Physical cross-linking does not introduce additional chemical substances, but it suffers from uneven cross-linking and low cross-linking degree. While chemical cross-linking can improve the volume stability of adhesive raw materials and prolong their degradation time, residual cross-linking agents often cause inflammatory reactions in surrounding tissues. Furthermore, as the material degrades, it releases cross-linking agents that continuously irritate surrounding tissues, hindering tissue healing. Moreover, chemical cross-linking often achieves excessively high cross-linking degrees, resulting in slow material degradation. Some studies have indicated that excessively prolonged degradation time can negatively impact tissue healing.
[0007] Research on how to achieve the best soft tissue repair results is ongoing, as exemplified by the following related patents:
[0008] Chinese invention patent (application number 202210620404.5) discloses an oral repair membrane and its preparation method, comprising a composite extracellular matrix layer and a collagen sponge layer disposed on the composite extracellular matrix layer. The collagen sponge layer is prepared by freeze-drying a collagen gel made from pulverized extracellular matrix powder or purified collagen powder. The extracellular matrix powder or purified collagen powder is obtained through protease digestion and purification, thus disrupting the natural cross-linking structure of the material and affecting its strength. Furthermore, since it is not cross-linked, the material collapses after absorbing water, exhibiting poor volume stability.
[0009] Chinese invention patent application No. 202310655636.9 discloses a porcine peritoneal decellularized matrix sponge scaffold and its preparation method. The sponge scaffold is prepared by degreasing and decellularizing porcine peritoneum, followed by crushing, enzymatic hydrolysis, purification, and cross-linking. The decellularized matrix is digested with proteases, which destroys the natural cross-linking structure of collagen fibers, reduces the overall strength of the material, and causes the degradation rate to be too fast. In addition, chemical cross-linking is used to enhance the strength of the material, which reduces the biocompatibility of the material.
[0010] Chinese invention patent (application number 202211143378.8) discloses a collagen matrix flap with excellent wet volume stability and its preparation method. Sodium periodate is added to a sodium alginate solution to prepare oxidized sodium alginate. Then, oxidized sodium alginate solution is added dropwise to a collagen solution to introduce chemical cross-linking. Finally, the flap is lyophilized by dialysis to obtain a collagen matrix flap with excellent wet volume stability. The material preparation process involves multiple chemical reactions and additional components, increasing the risk in practical applications.
[0011] In summary, current technologies cannot produce repair materials that combine both volumetric stability and stable soft tissue healing performance. Most suffer from drawbacks such as poor volumetric stability, excessively rapid degradation rates, or low biocompatibility. Furthermore, because domestically produced collagen sponge products currently cannot meet the requirements for long-term volumetric stability, most clinically used soft tissue replacement materials are sourced from abroad, resulting in very high prices and increasing the financial burden on patients.
[0012] Therefore, there is an urgent need to develop a soft tissue augmentation bio-substitute material with better volume stability and biocompatibility, which can not only shorten operation time and reduce postoperative complications, but also achieve clinical treatment efficacy comparable to or even better than that of autologous soft tissue grafts. Summary of the Invention
[0013] In view of this, the purpose of this application is to provide a method for preparing collagen matrix biomembrane, collagen matrix biomembrane and its application, so as to solve the shortcomings of existing soft tissue augmentation bio-substitute materials, such as poor volume stability, poor mechanical strength, easy material deformation and difficulty in fully matching the patient's injury site.
[0014] This invention provides a method for preparing a collagen matrix biomembrane, comprising:
[0015] S1: Prepare a decellularized matrix layer with a dense structure;
[0016] S2: Preparation of collagen suspension;
[0017] S3: After the collagen suspension is squeezed and injected into the mold to form, the decellularized matrix layer is moistened. The moistened decellularized matrix layer is spread evenly on the surface of the collagen suspension, the air bubbles are squeezed out, and it is left to stand so that the decellularized matrix layer and the collagen suspension are tightly combined.
[0018] S4: Freeze-dry the tightly bound decellularized matrix layer with the collagen suspension to obtain a composite freeze-dried layer;
[0019] S5: Physically cross-link the composite freeze-dried layer to obtain a collagen matrix biofilm.
[0020] Furthermore, the decellularized matrix layer with a dense structure is a multilayer composite decellularized matrix layer, wherein S1 further includes the following steps:
[0021] S11 Decellularization: A decellularized matrix is prepared by pretreatment, virus inactivation, defatting, decellularization, and drying of animal tissues of natural origin;
[0022] S12 composite: Vacuum pressing is used to composite 2-6 layers of decellularized matrix to obtain a multi-layer composite decellularized matrix layer.
[0023] Furthermore, the decellularized matrix layer with a dense structure is a recombinant decellularized matrix layer, wherein S1 further includes the following steps:
[0024] S101 Decellularization: A decellularized matrix is prepared by pretreatment, virus inactivation, defatting, decellularization, and drying of animal tissues of natural origin;
[0025] S102 pulverization: The decellularized matrix is pulverized into irregular particles with a particle size of 0.2mm-2mm by low-temperature grinding and suspended in pure water to make the mass percentage of the decellularized matrix particles 0.5%-3.0%. The pH value is adjusted to 2.5-3.0 with acid to fully swell the decellularized matrix particles and obtain a decellularized matrix suspension.
[0026] S103 Dehydration: Add sodium chloride powder to the decellularized matrix suspension until the sodium chloride concentration reaches 2.0-2.5 mol / L to obtain a white salting-out precipitate; soak the white salting-out precipitate in an organic solvent for 0.5-2 h to dehydrate, then wash with PBS buffer to remove the organic solvent and obtain collagen fibers;
[0027] S104 dispersion: Collagen fibers are suspended in PBS buffer to a collagen fiber mass percentage of 0.1%-6%, and a uniformly dispersed and fluffy collagen fiber suspension is obtained by mechanical stirring.
[0028] S105 film formation: The collagen fiber suspension is passed through a vacuum filtration device to uniformly trap the collagen fibers on a filter membrane with a pore size of 0.8μm. Filtration continues until the collagen fibers are dry and semi-transparent. The recombinant decellularized matrix layer with a thickness of 0.1-0.5mm is obtained by peeling.
[0029] Furthermore, the collagen suspension is prepared from gel-like collagen solution and collagen fiber solution by mixing 5-30 parts of gel-like collagen solution and 70-95 parts of collagen fiber solution, stirring evenly and defoaming under vacuum to obtain the collagen suspension.
[0030] Furthermore, the preparation steps of the gel-like collagen solution include:
[0031] S201 Decellularization: A decellularized matrix is prepared by pretreatment, virus inactivation, defatting, decellularization, and drying of animal tissues of natural origin;
[0032] S202 pulverization: After the decellularized matrix is cut into small pieces, it is suspended in pure water to make the mass percentage of the decellularized matrix 0.5%-3.0%. The pH is adjusted to 3.0-4.0 with acid. The decellularized matrix is pulverized into a gel state using a tissue homogenizer to obtain a gel-like collagen solution.
[0033] Furthermore, the preparation step of the collagen fiber solution includes:
[0034] S211 Decellularization: A decellularized matrix is prepared by pretreatment, virus inactivation, defatting, decellularization, and drying of animal tissues of natural origin;
[0035] S212 pulverization: The decellularized matrix is pulverized into irregular particles with a particle size of 0.2mm-2mm by low-temperature grinding and suspended in pure water to make the mass percentage of the decellularized matrix particles 0.5%-3.0%. The pH value is adjusted to 2.5-3.0 with acid to fully swell the decellularized matrix particles and obtain a decellularized matrix suspension.
[0036] S213 Dehydration: Add sodium chloride powder to the decellularized matrix suspension until the sodium chloride concentration reaches 2.0-2.5 mol / L to obtain a white salting-out precipitate; wash the white salting-out precipitate with PBS buffer and centrifuge to obtain concentrated collagen fibers;
[0037] S214 dispersion: Collagen fibers are placed in an acidic solution with a pH of 3.0-4.0, so that the mass percentage of collagen fibers is 1%-6%. The collagen fibers are then mechanically stirred to form a uniform dispersion with slight swelling, resulting in a collagen fiber solution.
[0038] Furthermore, the naturally derived tissues include the submucosa of the small intestine of pigs or cattle, the peritoneum of pigs or cattle, the pericardium of pigs or cattle, the bladder of pigs or cattle, and the dermis of pigs or cattle.
[0039] Furthermore, the organic solvent includes ethanol, acetone, diethyl ether, and isopropanol.
[0040] Further, the moistened decellularized matrix layer in step S3 is obtained by immersing the decellularized matrix layer in an acid with a pH of 3.0-4.0 for 10-30 minutes.
[0041] Furthermore, the acid includes hydrochloric acid, acetic acid, and citric acid.
[0042] Furthermore, the physical crosslinking in step S5 is a gradient thermal crosslinking, which involves placing the composite freeze-dried layer in a vacuum chamber, evacuating to less than -100 kPa, and maintaining it at 25℃-30℃ for 1-2 hours; then performing gradient temperature crosslinking, raising the temperature to 80℃-85℃ and holding it for 2-3 hours; continuing to raise the temperature to 100℃-105℃ and holding it for 2-3 hours; and finally raising the temperature to 120℃-125℃ and holding it for 24-48 hours.
[0043] The present invention also provides a collagen matrix biomembrane, which is prepared by the above-described preparation method.
[0044] The present invention also provides an application scenario for collagen matrix biomembrane, including applying the collagen matrix biomembrane prepared according to the above preparation method in any one or more of the following scenarios: guiding bone tissue regeneration in dentistry, increasing soft tissue volume in dentistry, preventing tissue adhesion, and repairing chronic wounds.
[0045] The beneficial effects of this invention are:
[0046] The present invention provides a collagen matrix biomembrane prepared by using natural animal tissue as raw material to prepare a decellularized matrix, and then further processing the decellularized matrix to obtain a collagen matrix biomembrane with a double-layer structure of a dense layer and a loose sponge layer.
[0047] (1) The structure of the dense layer was designed to match the different sources of animal tissues. When using pig or bovine small intestine or pig or bovine bladder tissue, the dense layer adopted a multi-layer composite decellularized matrix layer design, which improved the mechanical strength and degradability of the dense layer. When using pig or bovine peritoneum, pig or bovine pericardium, or pig or bovine dermis, the dense layer adopted a recombinant decellularized matrix layer design, which improved the degradability and maintained a certain mechanical strength.
[0048] (2) The loose layer is prepared by freeze-drying a collagen suspension, which is obtained from gel-like collagen solution and collagen fiber solution, and further processed from decellularized matrix. The gel-like collagen solution is a viscoelastic gel system prepared by thoroughly pulverizing the decellularized matrix. The system is homogeneous and contains more physical entanglements. After freeze-drying, it yields a relatively uniform pore structure. However, due to the disruption of most of the natural connections between fibers, its mechanical strength is low and it is easily degraded. In contrast, the decellularized matrix particles used in the preparation of the collagen fiber solution are larger, retaining more of the natural structure, resulting in high mechanical strength but a longer degradation time. However, the collagen fiber solution is an unstable dispersion system. When the collagen fiber solution is prepared into a freeze-dried sponge, the sponge structure is uneven and it easily collapses after absorbing water, due to the low interaction strength between collagen fibers. Therefore, we mix the gel-like collagen solution and the collagen fiber solution in a certain proportion. The gel-like collagen solution also acts as a thickener or binder, enhancing the interaction between collagen fibers, so that the final sponge structure possesses both mechanical properties and a uniform pore structure, and is less prone to collapse after absorbing liquid. At the same time, the addition of gel-like collagen will make the connection between the dense layer and the loose sponge layer more compact.
[0049] (3) During the preparation process, the moistened decellularized matrix layer is spread evenly on the surface of the collagen suspension, the air bubbles are gently squeezed out, and the mixture is left to stand so that the decellularized matrix layer and the collagen suspension are tightly bound together. The addition of gel-like collagen solution increases the viscosity of the collagen suspension, resulting in more physical entanglement between the decellularized matrix layer and the collagen suspension. The dense layer and the loose sponge layer are tightly bound together mainly through physical entanglement and hydrogen bonding.
[0050] (4) The collagen matrix biomembrane undergoes physical cross-linking treatment, which increases the interaction between collagen fibers, resulting in better volume stability and ensuring good biocompatibility. The collagen matrix membrane in this invention, through rational design and processing, overcomes the shortcomings of poor biological stability and mechanical properties in existing technologies. Even after absorbing water, the collagen matrix biomembrane treated with physical entanglement and cross-linking exhibits stable mechanical properties and shows no visible collapse under pressure. The collagen matrix membrane in this invention is a soft tissue augmentation bio-substitute material with better volume stability and biocompatibility, enabling better matching with the patient's wound and promoting healing. Attached Figure Description
[0051] To more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings used in the following description of the embodiments will be briefly introduced. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0052] Figure 1 This is a schematic cross-sectional view of a collagen matrix biomembrane according to this application;
[0053] Figure 2 This is a scanning electron microscope (SEM) image of the cross-sectional structure of the collagen matrix biomembrane prepared in Example 1.
[0054] Figure 3 This is a comparison chart of the wet volume stability test results of the collagen matrix biofilm and the Mucograft product in Example 1.
[0055] Numbers in the diagram
[0056] 1-Dense layer, 2-Sponge layer. Detailed Implementation
[0057] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0058] This invention provides a method for preparing a collagen matrix biomembrane, comprising:
[0059] S1: Prepare a decellularized matrix layer with a dense structure;
[0060] S2: Preparation of collagen suspension;
[0061] S3: After the collagen suspension is squeezed and injected into the mold to form, the decellularized matrix layer is moistened. The moistened decellularized matrix layer is spread evenly on the surface of the collagen suspension, the air bubbles are squeezed out, and it is left to stand so that the decellularized matrix layer and the collagen suspension are tightly combined.
[0062] S4: Freeze-dry the tightly bound decellularized matrix layer with the collagen suspension to obtain a composite freeze-dried layer;
[0063] S5: Physically cross-link the composite freeze-dried layer to obtain a collagen matrix biofilm.
[0064] The collagen matrix biomembrane obtained by the above preparation method in this invention has a bilayer structure. One layer is a dense, decellularized matrix layer, providing suture-compatible mechanical strength and protecting the wound in an open healing environment. The other layer is a loose, spongy layer, prepared from a collagen suspension through freeze-drying. This loose layer has a uniform porous structure, enabling rapid absorption of blood and body fluids, stabilizing blood clots, and promoting tissue healing. The collagen matrix membrane in this invention undergoes structural design and matching at both macroscopic and microscopic scales, resulting in a soft tissue augmentation bio-substitute material with better volume stability and biocompatibility. It better matches the patient's wound site, promoting healing.
[0065] In this invention, the decellularized matrix layer with a dense structure is a multilayer composite decellularized matrix layer or a recombinant decellularized matrix layer. The decellularized matrix is a naturally derived animal tissue prepared by a decellularization process.
[0066] In some preferred embodiments, the naturally derived animal tissue may be one of the following: the submucosa of the small intestine of pigs or cattle, the peritoneum of pigs or cattle, the pericardium of pigs or cattle, the bladder of pigs or cattle, or the dermis of pigs or cattle.
[0067] In some preferred embodiments, when the natural source animal tissue selected for the dense-structured decellularized matrix layer is the submucosa of the small intestine of pigs or cattle, or the bladder of pigs or cattle, it is necessary to prepare a multilayer composite decellularized matrix layer. That is, when the dense-structured decellularized matrix layer is a multilayer composite decellularized matrix layer, S1 further includes the following steps:
[0068] S11 Decellularization: A decellularized matrix is prepared by pretreatment, virus inactivation, defatting, decellularization, and drying of animal tissues of natural origin.
[0069] S12 composite: Multilayer decellularized matrix is vacuum-pressed and composited to obtain a multilayer composite decellularized matrix layer.
[0070] In some preferred embodiments, since the submucosa of the pig or cow small intestine and the pig or cow bladder become very thin after decellularization, the number of layers of the decellularized matrix is preferably 2-6 layers in order to control the mechanical strength and degradation time.
[0071] It should be noted that one of the technical problems to be solved in this invention is "a repair material that combines dimensional stability and stable soft tissue healing performance," which is the "balance between mechanical stability (high cross-linking degree) and stable soft tissue healing (low cross-linking degree)" mentioned in the background art. The single-layer submucosa of porcine or bovine small intestine and the decellularized matrix of porcine or bovine bladder are very thin, with a thickness of 0.02-0.03 mm. To obtain better degradability and mechanical strength, domestic and foreign products often use 6-12 layers of decellularized matrix composites while maintaining the uncross-linked natural collagen fiber structure. Since the collagen matrix biomembrane in this invention needs to undergo physical cross-linking treatment, to avoid the introduction of cross-linking that makes the submucosa of porcine or bovine small intestine and the decellularized matrix of porcine or bovine bladder difficult to degrade and affect tissue healing, the decellularized matrix composite layer in this invention is preferably 2-6 layers, more preferably 3-5 layers.
[0072] In some preferred embodiments, when the natural source animal tissue selected for the dense structured decellularized matrix layer is one of porcine or bovine peritoneum, porcine or bovine pericardium, or porcine or bovine dermis, the decellularized matrix layer needs to be reconstituted to prepare a recombinant decellularized matrix layer. That is, when the dense structured decellularized matrix layer is a recombinant decellularized matrix layer, S1 further includes the following steps:
[0073] S101 Decellularization: Decellularized matrix is prepared by pretreatment, virus inactivation, defatting, decellularization and drying of porcine or bovine peritoneum, porcine or bovine pericardium, and porcine or bovine dermal tissue.
[0074] S102 pulverization: The decellularized matrix is pulverized into irregular particles with a particle size of 0.2mm-2mm by low-temperature grinding and suspended in pure water, so that the mass percentage of the decellularized matrix particles is 0.5%-3.0%. The pH value of the pure water is adjusted to 2.5-3.0 with acid to fully swell the decellularized matrix particles and obtain a decellularized matrix suspension.
[0075] In some preferred embodiments, the acid is preferably one of hydrochloric acid, acetic acid, and citric acid;
[0076] S103 Dehydration: Add sodium chloride powder to the fully swollen decellularized matrix suspension until the sodium chloride concentration reaches 2.0-2.5 mol / L to obtain a white salting-out precipitate. Soak the white salting-out precipitate in an organic solvent for 0.5-2 h to dehydrate it, and then rinse it with PBS buffer (phosphate buffer solution) to obtain collagen fibers.
[0077] In some preferred embodiments, the organic solvent may be one of ethanol, acetone, diethyl ether, and isopropanol.
[0078] S104 Dispersion: Collagen fibers are suspended in PBS buffer to a collagen fiber mass percentage of 0.1%-6%, and a uniformly dispersed and fluffy collagen fiber suspension is obtained by mechanical stirring.
[0079] S105 membrane formation: The collagen fiber suspension is passed through a vacuum filtration device to uniformly trap the collagen fibers on a filter membrane with a pore size of 0.8μm. Filtration continues until the collagen fibers are dry and semi-transparent. The collagen fiber membrane with a thickness of 0.1-0.5mm is obtained by peeling and rinsing with pure water to obtain a recombinant decellularized matrix layer.
[0080] It should be noted that the preparation of the recombinant decellularized matrix layer is also due to one of the technical problems that needs to be solved in this invention: "a repair material that combines dimensional stability and stable soft tissue healing performance." Porcine or bovine peritoneum, porcine or bovine pericardium, and porcine or bovine dermal decellularized matrix are relatively thick, and a single-layer, non-crosslinked structure can usually meet the requirements for clinical use. Considering that the collagen matrix biomembrane in this invention requires physical crosslinking treatment, in order to avoid the introduction of crosslinking that would make the porcine or bovine peritoneum, porcine or bovine pericardium, and porcine or bovine dermal decellularized matrix difficult to degrade and affect tissue healing, a recombinant decellularized matrix layer was prepared in this invention. In the preparation of the recombinant decellularized matrix layer, decellularized matrix particles within a preferred particle size range swell sufficiently in an acid within a preferred pH range. Following salting-out precipitation, loose white collagen fibers are obtained. Further treatment with an organic solvent dehydrates and shrinks the collagen fibers, enhancing their mechanical strength and anti-swelling properties, thus preventing excessive swelling upon contact with water in the final recombinant decellularized matrix layer. The dehydrated collagen fibers are washed multiple times with PBS buffer to remove the organic solvent. The collagen fibers are then resuspended in PBS buffer at a mass percentage of 0.1%-6%. Since collagen fibers do not swell in PBS, mechanical stirring yields a uniformly dispersed and fluffy collagen fiber suspension. This series of processes forms an organic whole, aiming to ensure smooth membrane formation. To prevent collagen fibers from clogging the filter membrane pores, organic solvent treatment ensures sufficient shrinkage of the collagen fibers, preventing swelling. A large-pore size filter membrane of 0.8 μm is also selected. After negative pressure filtration, water passes through the filter membrane, while collagen fibers are retained on the membrane. Filtration continues until the collagen fibers form a dry, semi-transparent membrane, ultimately forming a collagen fiber membrane of a certain thickness. To maintain reasonable mechanical strength and degradation time, the thickness of the collagen fiber membrane is preferably 0.06 mm to 0.18 mm.
[0081] The collagen suspension in this invention is prepared from gel-like collagen solution and collagen fiber solution. Both the gel-like collagen solution and the collagen fiber solution are prepared from decellularized matrix of animal tissues of natural origin. The natural animal tissues can be one of the following: submucosa of pig or bovine small intestine, peritoneum of pig or bovine, pericardium of pig or bovine, bladder of pig or bovine, or dermis of pig or bovine.
[0082] Specifically, the preparation steps of the gel-like collagen solution include:
[0083] S201 Decellularization: A decellularized matrix is prepared by pretreatment, virus inactivation, defatting, decellularization, and drying of animal tissues of natural origin;
[0084] S202 pulverization: After the decellularized matrix is cut into small pieces, it is suspended in pure water to make the mass percentage of the decellularized matrix 0.5%-3.0%. The pH value of the pure water is adjusted to 3.0-4.0 with acid. The decellularized matrix is pulverized into a gel state using a tissue homogenizer to obtain a gel-like collagen solution.
[0085] In some preferred embodiments, since the decellularized matrix can swell in an acidic solution, and with the strong shearing and mixing effect of the tissue homogenizer, the decellularized matrix is pulverized into extremely small particles and further swells, causing the solution viscosity to gradually increase, and finally a viscous gel-like collagen solution is obtained.
[0086] In some preferred embodiments, the acid may be one of hydrochloric acid, acetic acid, and citric acid.
[0087] In some preferred embodiments, the mass percentage of decellularized matrix in pure water is preferably 0.5%-3.0%. This is because when the mass percentage of decellularized matrix is less than 0.5%, the final collagen solution is a fluid solution with low viscosity, which will adversely affect the subsequent preparation process of collagen suspension. When the mass percentage of decellularized matrix is greater than 3.0%, the final collagen solution will lose its fluidity due to excessive concentration, resulting in some swollen particles not being fully pulverized, thus affecting the pulverization effect. The viscosity of the final gel-like collagen solution is related to the pH value. Within a certain range, the lower the pH value, the higher the viscosity. To avoid the gel-like collagen solution having excessive viscosity and affecting the pulverization effect, the pH range is preferably 3.0-4.0.
[0088] In some preferred embodiments, the preparation steps of the collagen fiber solution are as follows:
[0089] S211 Decellularization: A decellularized matrix is prepared by pretreatment, virus inactivation, defatting, decellularization, and drying of animal tissues of natural origin;
[0090] S212 pulverization: The decellularized matrix is pulverized into irregular particles with a particle size of 0.2mm-2mm by low-temperature grinding and suspended in pure water, so that the mass percentage of the decellularized matrix particles is 0.5%-3.0%. The pH value of the pure water is adjusted to 2.5-3.0 with acid to fully swell the decellularized matrix particles and obtain a decellularized matrix suspension.
[0091] S213 Dehydration: Add sodium chloride powder to the decellularized matrix suspension until the sodium chloride concentration reaches 2.0-2.5 mol / L to obtain a white salting-out precipitate; wash the white salting-out precipitate with PBS buffer and centrifuge to obtain concentrated collagen fibers;
[0092] S214 dispersion: Collagen fibers are placed in an acid with a pH of 3.0-4.0, so that the mass percentage of collagen fibers is 1%-6%. The collagen fibers are then mechanically stirred to form a slightly swollen and uniformly dispersed state, resulting in a collagen fiber solution. The acid can be one of hydrochloric acid, acetic acid, or citric acid.
[0093] It should be noted that during the preparation of collagen fiber solution, the pulverized decellularized matrix particles swell in an acidic solution with a pH of 2.5-3.0, and then undergo salting-out precipitation to obtain loose white collagen fibers. In order to maintain the natural structure of the decellularized matrix to a certain extent, the particle size of the pulverized decellularized matrix is preferably 0.2mm-2mm.
[0094] In some preferred embodiments, to avoid separation of collagen fiber liquid, the collagen fibers are dispersed in an acidic solution with a pH of 3.0-4.0 to allow the collagen fibers to swell slightly, and then uniformly dispersed by mechanical stirring.
[0095] In some preferred embodiments, in order to match the gel-like collagen solution, the pH value of the collagen fiber solution should be the same as that of the gel-like collagen solution.
[0096] It should be noted that the preparation process of the collagen fiber solution differs from that of the recombinant decellularized matrix layer described above. Here, the salted-out collagen fibers are not dehydrated using organic solvents. Organic solvent treatment dehydrates the collagen fibers, increasing their mechanical properties, but it weakens their swelling effect in acidic solutions. Furthermore, the purpose of preparing the collagen fiber solution is to blend it with the gel-like collagen solution to create a uniform and loosely porous sponge layer, while the recombinant decellularized matrix layer prioritizes mechanical properties; therefore, organic solvent dehydration is unnecessary here.
[0097] After the gel-like collagen solution and collagen fiber solution are prepared separately, they are mixed in proportion, stirred evenly, and defoamed under vacuum to obtain a collagen suspension.
[0098] In some preferred embodiments, 5-30 parts of gel-like collagen solution and 70-95 parts of collagen fiber solution are taken, and the two are stirred evenly and defoamed under vacuum to obtain a collagen suspension.
[0099] In some preferred embodiments, the gel-like collagen solution is a viscoelastic gel system prepared by thoroughly pulverizing the decellularized matrix. The system is homogeneous and contains more physical entanglements. After freeze-drying, it achieves a relatively uniform pore structure. However, because it disrupts most of the natural connections between fibers, its mechanical strength is low and it is easily degraded. In contrast, the decellularized matrix particles used in the preparation of collagen fiber solution are larger, retaining more of the natural structure, resulting in high mechanical strength but a longer degradation time. However, collagen fiber solution is an unstable dispersion system. When collagen fiber solution is prepared into a freeze-dried sponge alone, the sponge structure is uneven and easily collapses under pressure after absorbing water due to the low inter-fiber bonding strength. Therefore, we mix the gel-like collagen solution and collagen fiber solution in a certain proportion, where the gel-like collagen solution also acts as a thickener or binder, so that the final sponge structure possesses both mechanical properties and a uniform pore structure, making it less prone to collapse after absorbing liquid. Simultaneously, the addition of the gel-like collagen solution also makes the connection between the dense layer and the loose sponge layer more compact.
[0100] Further, the collagen suspension is extruded into a mold for shaping. The decellularized matrix layer is immersed in an acidic solution with a pH of 3.0-4.0 for 10-30 minutes to obtain a moistened decellularized matrix layer. This moistened decellularized matrix layer is then spread evenly on the surface of the collagen suspension, and air bubbles are gently squeezed out. The mixture is allowed to stand to allow the moistened decellularized matrix layer to tightly bond with the collagen suspension. The addition of gel-like collagen increases the viscosity of the collagen suspension, creating more physical entanglement forces between the decellularized matrix layer and the collagen suspension. At this point, the dense layer and the loose spongy layer are tightly bound together primarily through physical entanglement and hydrogen bonding.
[0101] In some preferred embodiments, the collagen matrix biomembrane in this application is obtained after physical cross-linking. The physical cross-linking is a gradient thermal cross-linking process, which involves placing the composite freeze-dried layer in a vacuum chamber, evacuating to less than -100 kPa, and maintaining the temperature at 25°C-30°C for 1-2 hours; then performing gradient temperature cross-linking, raising the temperature to 80°C-85°C and holding for 2-3 hours; further raising the temperature to 100°C-105°C and holding for 2-3 hours; and finally raising the temperature to 120°C-125°C and holding for 24-48 hours. This physical cross-linking treatment increases the interaction between collagen fibers, resulting in better volume stability and ensuring good biocompatibility.
[0102] As described in the background section, the sponge layer of commercially available Mucograft products is a freeze-dried collagen fiber structure, which collapses upon absorbing water and applying pressure. In this invention, however, the introduction of more physical entanglement and gradient thermal crosslinking significantly enhances the interaction strength between collagen fibers, fundamentally improving the volume stability and degradability of the sponge layer. In this invention, the collagen fibers in the collagen fiber solution undergo swelling and salting-out processes, causing them to shrink. Due to the lack of inter-fiber connections, the freeze-dried sponge easily collapses and disintegrates after absorbing liquid. To address this problem, this technology introduces gradient thermal crosslinking. Gradient thermal crosslinking is a physical crosslinking process where the carboxyl and amino groups of adjacent amino acid side chains undergo condensation reactions to form ester and amide bonds. This crosslinking method does not excessively damage the triple helix structure of collagen and does not introduce additional chemical crosslinking agents. However, experiments have shown that the shrunken collagen fiber structure also means fewer active groups, resulting in a low crosslinking density after gradient thermal crosslinking, which fails to improve the collapse phenomenon after liquid absorption. Therefore, this technology further introduces a gel-like collagen solution, which contains more physically entangled structures. After being fully mixed with collagen fibers, it can act as a bridge, increasing the interaction between collagen fibers and connecting them into a whole. After gradient thermal cross-linking, more ester bonds and amide bonds are formed. The resulting collagen matrix biomembrane does not show significant collapse after liquid absorption and has excellent volume stability.
[0103] The present invention also provides a collagen matrix biomembrane prepared by the above method, comprising a dense layer 1 and a loose sponge layer 2. The dense layer 1 comprises 2-6 layers of composite decellularized matrix or recombinant decellularized matrix. The dense layer 1 and the loose sponge layer 2 are tightly connected by physical entanglement, hydrogen bonding and physical cross-linking. The loose sponge layer 2 is used to adhere tightly to the soft tissue defect area.
[0104] The loose sponge layer 2 is a porous, loose collagen layer, which includes a gel-like collagen liquid freeze-dried layer and a collagen fiber liquid freeze-dried layer.
[0105] In some preferred embodiments, the loose sponge layer 2 is obtained by freeze-drying a mixture of gel-like collagen solution and collagen fiber solution, with the freeze-dried gel-like collagen solution layer and the freeze-dried collagen fiber solution layer interwoven. Physical cross-linking further enhances the mechanical strength and volume stability of the collagen matrix biomembrane. In use, the dense layer 1 provides reliable suturing force and allows open wound healing; the loose sponge layer 2, facing the soft tissue defect area, can stabilize blood clots and promote tissue repair. Due to its excellent hydrophilicity, the loose sponge layer 2 can rapidly absorb body fluids at the tissue defect site, thus adhering tightly to the defect.
[0106] This application also provides an application of collagen matrix biomembrane, including applying the collagen matrix biomembrane prepared by the above preparation method in any one or more of the following scenarios: guiding bone tissue regeneration in dentistry, increasing soft tissue volume in dentistry, preventing tissue adhesion, and repairing chronic wounds.
[0107] To further illustrate the present invention, the following describes in detail a collagen matrix biomembrane and its preparation method provided in the present invention with reference to embodiments.
[0108] All raw materials and reagents used in the following examples are commercially available.
[0109] Example 1
[0110] In this embodiment, the naturally derived tissue was selected from the submucosa of porcine small intestine. First, a decellularized matrix was prepared. Excess tissue was removed from the porcine small intestine, and the tissue was soaked in a 0.1% peracetic acid solution for 1 hour, followed by rinsing with running water. The intestine was then shaken and washed for 1 hour with a mixed solution of 0.05% trypsin and 0.05% sodium dodecyl sulfate, followed by rinsing with running water again. Finally, the tissue was degreased by soaking in 75% isopropanol, and freeze-dried to obtain the decellularized submucosa matrix of porcine small intestine. The above pretreatment, virus inactivation, degreasing, decellularization, and drying steps are conventional steps in the prior art, and their details are not further elaborated here.
[0111] The following describes the preparation of a collagen matrix biomembrane:
[0112] ① Preparation of a dense decellularized matrix layer: Six layers of porcine small intestinal submucosa decellularized matrix were vacuum-pressed and composited to obtain a multi-layer composite decellularized matrix layer.
[0113] ②Preparation of collagen suspension:
[0114] First, prepare a gel-like collagen solution by cutting up the decellularized matrix of the submucosa of the pig small intestine and suspending it in pure water to make the mass percentage of the decellularized matrix 1.0%. Adjust the pH of the pure water to 3.0 with acetic acid and then use a tissue homogenizer to pulverize the decellularized matrix into a gel-like state to obtain a gel-like collagen solution.
[0115] Then, a collagen fiber solution was prepared. The decellularized submucosa matrix of porcine small intestine was pulverized into irregular particles with a particle size of 0.2 mm-2 mm by low-temperature grinding and suspended in pure water to achieve a mass percentage of 3.0% for the decellularized matrix particles. The pH was adjusted to 3.0 with acetic acid to allow the decellularized matrix particles to fully swell, resulting in a decellularized matrix suspension. Sodium chloride powder was added to the decellularized matrix suspension until the sodium chloride concentration reached 2.5 mol / L, resulting in a white salt-out precipitate. The white salt-out precipitate was washed with PBS buffer and centrifuged to obtain concentrated collagen fibers. The collagen fibers were placed in acetic acid at pH 3.0 to achieve a mass percentage of 3% for the collagen fibers. Mechanical stirring was used to achieve a slightly swollen and uniformly dispersed collagen fiber solution.
[0116] Collagen suspension is prepared from gel-like collagen solution and collagen fiber solution. 20 parts gel-like collagen solution and 80 parts collagen fiber solution are mixed, stirred evenly and defoamed under vacuum to obtain collagen suspension.
[0117] ③ The collagen suspension is squeezed and injected into the mold to form a shape. The multilayer composite porcine small intestinal submucosa decellularized matrix layer is placed in acetic acid at pH 3.0 and moistened for 10 minutes. The moistened decellularized matrix is spread evenly on the surface of the collagen suspension, and the air bubbles are squeezed out. The layer is left to stand so that the decellularized matrix layer and the collagen suspension are tightly combined.
[0118] The tightly bound decellularized matrix layer and collagen suspension were freeze-dried to obtain a composite freeze-dried layer. The composite freeze-dried layer was then placed in a vacuum chamber, evacuated to -110 kPa, and held at 25°C for 2 hours. Gradual temperature cross-linking was then performed: the temperature was increased to 80°C and held for 3 hours; the temperature was further increased to 100°C and held for 3 hours; finally, the temperature was increased to 120°C and held for 48 hours. After cooling to room temperature, the collagen matrix biomembrane was removed.
[0119] Example 2
[0120] In this embodiment, porcine pericardium was selected as the naturally sourced tissue. First, a decellularized matrix was prepared. Excess tissue was removed from the porcine pericardium tissue, and it was soaked in a 0.1% peracetic acid solution for 1 hour, followed by rinsing with running water. The tissue was then shaken and washed for 1 hour with a mixed solution of 0.05% trypsin and 0.05% sodium dodecyl sulfate, and then rinsed again with running water. Finally, it was degreased by soaking in 75% isopropanol and freeze-dried to obtain the decellularized porcine pericardium matrix.
[0121] The following describes the preparation of a collagen matrix biomembrane:
[0122] ① Preparation of a dense decellularized matrix layer: Porcine pericardial decellularized matrix was pulverized into irregular particles with a particle size of 0.2 mm-2 mm by low-temperature grinding and suspended in pure water to a mass percentage of 0.5%. The pH of the pure water was adjusted to 2.5 with hydrochloric acid to fully swell the decellularized matrix particles, resulting in a decellularized matrix suspension. Sodium chloride powder was added to the decellularized matrix suspension until the sodium chloride concentration reached 2.0 mol / L, resulting in a white salt-out precipitate. The white salt-out precipitate was... After soaking the material in acetone for 0.5 h to dehydrate, it was rinsed with PBS buffer to remove residual acetone, yielding collagen fibers. The collagen fibers were then suspended in PBS buffer to a mass percentage of 0.1%, and mechanically stirred to obtain a uniformly dispersed and fluffy collagen fiber suspension. The collagen fiber suspension was then passed through a vacuum filtration device to uniformly trap the collagen fibers on a 0.8 μm pore size filter membrane. Filtration continued until the collagen fibers formed a dry, semi-transparent membrane, which was then peeled off to obtain a recombinant decellularized matrix layer with a thickness of 0.1 mm.
[0123] ② Preparation of collagen suspension: First, prepare gel-like collagen solution by cutting the decellularized matrix of porcine pericardium into small pieces and suspending it in pure water to make the mass percentage of the decellularized matrix 0.5%. Adjust the pH to 4.0 with acetic acid and use a tissue homogenizer to pulverize the decellularized matrix into a gel-like state to obtain gel-like collagen solution.
[0124] Then, a collagen fiber solution was prepared. Porcine pericardial decellularized matrix was pulverized into irregular particles with a particle size of 0.2 mm-2 mm by low-temperature grinding and suspended in pure water to achieve a mass percentage of 3.0% for the decellularized matrix particles. The pH was adjusted to 3.0 with acetic acid to allow the decellularized matrix particles to fully swell, resulting in a decellularized matrix suspension. Sodium chloride powder was added to the decellularized matrix suspension until the sodium chloride concentration reached 2.5 mol / L, resulting in a white salt-out precipitate. The white salt-out precipitate was washed with PBS buffer and centrifuged to obtain concentrated collagen fibers. The collagen fibers were placed in acetic acid at pH 4.0 to achieve a mass percentage of 6% for the collagen fibers. Mechanical stirring was used to achieve a slightly swollen and uniformly dispersed collagen fiber solution.
[0125] Collagen suspension is prepared from gel-like collagen solution and collagen fiber solution. 5 parts gel-like collagen solution and 95 parts collagen fiber solution are mixed, stirred evenly, and defoamed under vacuum to obtain collagen suspension.
[0126] ③ The collagen suspension is squeezed and injected into the mold to form a shape. The recombinant porcine pericardial decellularized matrix layer is moistened in acetic acid at pH 4.0 for 10 minutes. The moistened decellularized matrix is spread evenly on the surface of the collagen suspension, and the air bubbles are squeezed out. The layer is left to stand so that the decellularized matrix layer and the collagen suspension are tightly combined.
[0127] ④ The tightly bound decellularized matrix layer and collagen suspension were freeze-dried to obtain a composite freeze-dried layer. The composite freeze-dried layer was then placed in a vacuum chamber, evacuated to -110 kPa, and held at 30°C for 1 hour. Gradual temperature increase was then applied for cross-linking: the temperature was increased to 85°C and held for 2 hours; the temperature was further increased to 105°C and held for 2 hours; finally, the temperature was increased to 125°C and held for 24 hours. After cooling to room temperature, the collagen matrix biomembrane was removed.
[0128] Example 3
[0129] In this embodiment, decellularized submucosa matrix of porcine small intestine and decellularized pericardium matrix were prepared using the methods described in Examples 1 and 2.
[0130] The following describes the preparation of a collagen matrix biomembrane:
[0131] ① Preparation of a dense decellularized matrix layer: Two layers of wet decellularized matrix from the submucosa of porcine small intestine were vacuum-pressed together to obtain a multilayer composite decellularized matrix layer.
[0132] ② Preparation of collagen suspension: First, prepare gel-like collagen solution by cutting the decellularized matrix of porcine pericardium into small pieces and suspending it in pure water to make the mass percentage of the decellularized matrix 2%. Adjust the pH to 4.0 with acetic acid and use a tissue homogenizer to pulverize the decellularized matrix into a gel-like state to obtain gel-like collagen solution.
[0133] Then, a collagen fiber solution was prepared. Porcine pericardial decellularized matrix was pulverized into irregular particles with a particle size of 0.2 mm-2 mm by low-temperature grinding and suspended in pure water to achieve a mass percentage of 2.0% for the decellularized matrix particles. The pH of the pure water was adjusted to 2.5 with acetic acid to allow the decellularized matrix particles to fully swell, resulting in a decellularized matrix suspension. Sodium chloride powder was added to the decellularized matrix suspension until the sodium chloride concentration reached 2.0 mol / L, resulting in a white salting-out precipitate. The white salting-out precipitate was washed with PBS buffer and centrifuged to obtain concentrated collagen fibers. The collagen fibers were placed in acetic acid at pH 4.0 to achieve a mass percentage of 4% for the collagen fibers. Mechanical stirring was used to achieve a slightly swollen and uniformly dispersed collagen fiber solution.
[0134] Collagen suspension is prepared from gel-like collagen solution and collagen fiber solution. 10 parts gel-like collagen solution and 90 parts collagen fiber solution are mixed, stirred evenly and defoamed under vacuum to obtain collagen suspension.
[0135] ③ The collagen suspension is squeezed and injected into the mold to form a shape. The multilayer composite porcine small intestinal submucosa decellularized matrix layer is placed in acetic acid at pH 4.0 and moistened for 30 minutes. The moistened decellularized matrix is spread evenly on the surface of the collagen suspension, and the air bubbles are squeezed out. The layer is left to stand so that the decellularized matrix layer and the collagen suspension are tightly combined.
[0136] ④ The tightly bound decellularized matrix layer and collagen suspension were freeze-dried to obtain a composite freeze-dried layer. The composite freeze-dried layer was then placed in a vacuum chamber and evacuated to less than -100 kPa, and kept at 30°C for 1 hour. Gradual temperature cross-linking was then performed: the temperature was increased to 80°C and held for 2 hours; the temperature was further increased to 100°C and held for 2 hours; the temperature was increased to 120°C and held for 36 hours. After cooling to room temperature, the collagen matrix biomembrane was removed.
[0137] Example 4
[0138] In this embodiment, decellularized submucosa matrix of porcine small intestine and decellularized pericardium matrix were prepared using the methods described in Examples 1 and 2.
[0139] The following describes the preparation of a collagen matrix biomembrane:
[0140] ① Preparation of a dense decellularized matrix layer: Porcine pericardial decellularized matrix was pulverized into irregular particles with a particle size of 0.2 mm-2 mm by low-temperature grinding and suspended in pure water to make the mass percentage of decellularized matrix particles 3.0%. The pH of the pure water was adjusted to 3.0 with hydrochloric acid to fully swell the decellularized matrix particles, resulting in a decellularized matrix suspension. Sodium chloride powder was added to the decellularized matrix suspension until the sodium chloride concentration reached 2.5 mol / L, resulting in a white salting-out precipitate. The white salting-out precipitate was soaked in ethanol for 2 h to dehydrate, and then rinsed with PBS buffer to remove residual ethanol, resulting in collagen fibers. The collagen fibers were suspended in PBS buffer to make the mass percentage of collagen fibers 6%, and a uniformly dispersed and fluffy collagen fiber suspension was obtained by mechanical stirring. The collagen fiber suspension was passed through a vacuum filtration device to uniformly trap the collagen fibers on a filter membrane with a pore size of 0.8 μm. Filtration continued until the collagen fibers were in the form of a dry, semi-transparent membrane, and then peeled off to obtain a recombinant decellularized matrix layer with a thickness of 0.5 mm.
[0141] ②Preparation of collagen suspension:
[0142] First, prepare a gel-like collagen solution by cutting up the decellularized matrix of the submucosa of the pig small intestine and suspending it in pure water to make the mass percentage of the decellularized matrix 3.0%. Adjust the pH of the pure water to 3.0 with acetic acid and then use a tissue homogenizer to pulverize the decellularized matrix into a gel-like state to obtain a gel-like collagen solution.
[0143] Then, a collagen fiber solution was prepared. The decellularized submucosa matrix of porcine small intestine was pulverized into irregular particles with a particle size of 0.2 mm-2 mm by low-temperature grinding and suspended in pure water to a mass percentage of 0.5%. The pH of the pure water was adjusted to 2.5 with acetic acid to allow the decellularized matrix particles to fully swell, resulting in a decellularized matrix suspension. Sodium chloride powder was added to the decellularized matrix suspension until the sodium chloride concentration reached 2.0 mol / L, resulting in a white salting-out precipitate. The white salting-out precipitate was washed with PBS buffer and centrifuged to obtain concentrated collagen fibers. The collagen fibers were placed in acetic acid at pH 3.0 to a mass percentage of 1%, and mechanical stirring was used to achieve a slightly swollen and uniformly dispersed collagen fiber solution.
[0144] Collagen suspension is prepared from gel-like collagen solution and collagen fiber solution. 30 parts gel-like collagen solution and 70 parts collagen fiber solution are mixed, stirred evenly and defoamed under vacuum to obtain collagen suspension.
[0145] ③ The collagen suspension is squeezed into the mold to form a shape. The multilayer composite porcine small intestinal submucosa decellularized matrix layer is soaked in acetic acid at pH 3.0 for 30 minutes. The moistened decellularized matrix is spread evenly on the surface of the collagen suspension, and the air bubbles are squeezed out. The layer is left to stand so that the decellularized matrix layer is tightly combined with the collagen suspension.
[0146] ④ The tightly bound decellularized matrix layer and collagen suspension were freeze-dried to obtain a composite freeze-dried layer. The composite freeze-dried layer was then placed in a vacuum chamber, evacuated to -110 kPa, and kept at 25°C for 2 hours. Gradual temperature cross-linking was then performed: the temperature was increased to 80°C and held for 3 hours; the temperature was further increased to 100°C and held for 3 hours; finally, the temperature was increased to 120°C and held for 48 hours. After cooling to room temperature, the collagen matrix biomembrane was removed.
[0147] Comparative Example 1
[0148] In this embodiment, the method described in Example 1 was used to prepare a layered decellularized matrix of the porcine small intestinal submucosa. Compared with Example 1, the collagen suspension in Comparative Example 1 was replaced with collagen fiber solution.
[0149] The following describes the preparation of a collagen matrix biomembrane:
[0150] ① Preparation of a dense decellularized matrix layer: Six layers of wet decellularized matrix from the submucosa of porcine small intestine were vacuum-pressed and composited to obtain a multilayer composite decellularized matrix layer.
[0151] ②Preparation of collagen fiber solution:
[0152] Collagen fiber solution was prepared by grinding the decellularized submucosa matrix of porcine small intestine into irregular particles with a particle size of 0.2 mm-2 mm using low-temperature grinding, and suspending it in pure water to make the mass percentage of decellularized matrix particles 3.0%. The pH of the pure water was adjusted to 3.0 with acetic acid to allow the decellularized matrix particles to fully swell, resulting in a decellularized matrix suspension. Sodium chloride powder was added to the decellularized matrix suspension until the sodium chloride concentration reached 2.5 mol / L, resulting in a white salting-out precipitate. The white salting-out precipitate was washed with PBS buffer and centrifuged to obtain concentrated collagen fibers. The collagen fibers were placed in acetic acid at pH 3.0 to make the mass percentage of collagen fibers 3%, and mechanical stirring was used to make the collagen fibers exhibit a slightly swollen and uniformly dispersed state, resulting in a collagen fiber solution.
[0153] ③ The collagen fiber liquid is squeezed and injected into the mold to form a shape. The multilayer composite porcine small intestinal submucosa decellularized matrix layer is placed in acetic acid with a pH of 3.0 and moistened for 10 minutes. The moistened decellularized matrix is spread evenly on the surface of the collagen suspension, and the air bubbles are squeezed out. It is left to stand so that the decellularized matrix layer and the collagen fiber liquid are tightly combined.
[0154] ④ The tightly bound decellularized matrix layer and collagen suspension were freeze-dried to obtain a composite freeze-dried layer. The composite freeze-dried layer was then placed in a vacuum chamber, evacuated to -110 kPa, and kept at 25°C for 2 hours. Gradual temperature cross-linking was then performed: the temperature was increased to 80°C and held for 3 hours; the temperature was further increased to 100°C and held for 3 hours; finally, the temperature was increased to 120°C and held for 48 hours. After cooling to room temperature, the collagen matrix biomembrane was removed.
[0155] Comparative Example 2
[0156] In this embodiment, the method described in Example 1 was used to prepare a layered decellularized submucosal matrix of porcine small intestine. Compared with Example 1, the collagen matrix biomembrane in Comparative Example 2 was not cross-linked.
[0157] The following describes the preparation of a collagen matrix biomembrane:
[0158] ① Preparation of a dense decellularized matrix layer: Six layers of decellularized matrix from the submucosa of porcine small intestine were vacuum-pressed and composited to obtain a multilayer composite decellularized matrix layer.
[0159] ②Preparation of collagen suspension:
[0160] First, prepare a gel-like collagen solution by cutting up the decellularized matrix of the submucosa of the pig small intestine and suspending it in pure water to make the mass percentage of the decellularized matrix 1.0%. Adjust the pH of the pure water to 3.0 with acetic acid and then use a tissue homogenizer to pulverize the decellularized matrix into a gel-like state to obtain a gel-like collagen solution.
[0161] Then, a collagen fiber solution was prepared. The decellularized submucosa matrix of porcine small intestine was pulverized into irregular particles with a particle size of 0.2 mm-2 mm by low-temperature grinding and suspended in pure water to a mass percentage of 3.0%. The pH of the pure water was adjusted to 3.0 with acetic acid to allow the decellularized matrix particles to fully swell, resulting in a decellularized matrix suspension. Sodium chloride powder was added to the decellularized matrix suspension until the sodium chloride concentration reached 2.5 mol / L, resulting in a white salting-out precipitate. The white salting-out precipitate was washed with PBS buffer and centrifuged to obtain concentrated collagen fibers. The collagen fibers were placed in acetic acid at pH 3.0 to a mass percentage of 3%, and mechanical stirring was used to achieve a slightly swollen and uniformly dispersed collagen fiber solution.
[0162] Collagen suspension is prepared from gel-like collagen solution and collagen fiber solution. 20 parts gel-like collagen solution and 80 parts collagen fiber solution are mixed, stirred evenly and defoamed under vacuum to obtain collagen suspension.
[0163] ③ The collagen suspension is squeezed and injected into the mold to form a shape. The multilayer composite porcine small intestinal submucosa decellularized matrix layer is placed in acetic acid at pH 3.0 and moistened for 10 minutes. The moistened decellularized matrix is spread evenly on the surface of the collagen suspension, and the air bubbles are squeezed out. The layer is left to stand so that the decellularized matrix layer and the collagen suspension are tightly combined.
[0164] ④ The tightly bound decellularized matrix layer and collagen suspension are freeze-dried to obtain a composite freeze-dried layer. At this time, the composite freeze-dried layer is an uncrosslinked collagen matrix biomembrane.
[0165] Comparative Test
[0166] ① Cytotoxicity test: The collagen matrix biomembranes prepared in Example 1 and Comparative Examples 1 and 2 were tested using the MTT assay according to the national standard GB / T16886.5-2017 "Biological evaluation of medical devices - Part 5: In vitro cytotoxicity test". L929 mouse fibroblasts were used. The test samples of each group were added to serum-containing culture medium and extracted at 37°C for 24 hours. The extract was then added to the cells and cultured for 24 hours. The cytotoxicity was detected by the MTT assay (n=3). The test results are shown in Table 1:
[0167] Table 1. Cytotoxicity test results of collagen matrix biomembranes prepared in Example 1 and Comparative Examples 1 and 2
[0168] Example 1 95.60 Comparative Example 1 94.47 Comparative Example 2 95.63
[0169] Table 1 shows that the cell viability rates of Sample 1, Comparative Examples 1 and 2 were 93.60%, 94.47%, and 95.63%, respectively. The cell viability results in Sample 1 and Comparative Example 1 were similar, while the cell viability rate in Comparative Example 2 was slightly higher due to the absence of cross-linking treatment. Because the proportion of denatured collagen fibers during gradient thermal cross-linking is very small, the collagen matrix biomembrane after gradient thermal cross-linking still exhibits very low cytotoxicity.
[0170] ② In vitro degradation test: The samples obtained in Example 1, Comparative Examples 1 and 2 were weighed and recorded as W0. Under aseptic conditions at 37°C, the samples were immersed in PBS buffer solution containing 20 U / mL collagenase and allowed to stand. Samples were taken at 6h, 8h, and 12h, vacuum dried, and weighed, recorded as W1. The degradation rate was calculated using the following formula, and the degradation calculation results are shown in Table 2:
[0171]
[0172] Table 2. In vitro degradation detection results of collagen matrix biomembranes prepared in Example 1 and Comparative Examples 1 and 2
[0173] Example 1 60.44% 78.32% 100% Comparative Example 1 58.36% 79.92% 100% Comparative Example 2 70.17% 90.29% 100%
[0174] The results showed that Example 1 and Comparative Example 1 had similar in vitro degradation processes, while Comparative Example 2 degraded faster because it did not undergo cross-linking treatment.
[0175] ③ Tensile strength test: Cut the product into strips with a width of 10mm, clamp the two ends of the product with fixtures, turn on the tensile testing machine, and test the tensile strength (MPa) at a speed of 100mm / min. The results are shown in Table 3:
[0176] Table 3. Tensile strength test results of collagen matrix biomembranes prepared in Example 1 and Comparative Examples 1 and 2
[0177]
[0178] The results showed that the overall tensile strength of the collagen matrix biomembrane was high, which is attributed to the high mechanical strength of the 6-layer composite decellularized matrix. However, due to the decellularized matrix being obtained from natural tissue processing, there was structural inhomogeneity, resulting in slight variations in tensile strength. The sponge layer, being a relatively homogeneous structure, was tested separately to analyze the effects of gel-like collagen solution and gradient thermal crosslinking treatment on the mechanical properties of the final product. The results for the sponge layer showed that the collagen matrix biomembrane in Example 1 had the highest tensile strength, followed by the collagen matrix biomembrane in Comparative Example 1, while the tensile strength in Comparative Example 2 was the lowest. The collagen suspension in Comparative Example 1 used only collagen fiber solution without adding gel-like collagen solution, resulting in a lack of entanglement between collagen fibers in the sponge layer, leading to significantly lower tensile strength compared to Example 1. The collagen matrix biomembrane in Comparative Example 2, lacking crosslinking treatment, exhibited lower tensile strength. These results indicate that the collagen matrix biomembrane with added gel-like collagen solution and gradient thermal crosslinking treatment possesses better mechanical strength.
[0179] ④ Seam tear strength test: Cut the product into strips 10mm wide. Pass a 4-0 gauge suture through the product 3mm-5mm from the short edge. Fold the suture in half and tie a knot approximately 5cm from the perforation to prevent it from coming loose. Fix the unthreaded end and the threaded end of the product to a tensile testing machine. Tensile speed is 100mm / min until the product tears. The maximum tensile load is recorded as the tear strength (N) of the product. Results are shown in Table 4.
[0180] Table 4. Suture tear strength test results of collagen matrix biomembranes prepared in Example 1 and Comparative Examples 1 and 2
[0181] Suture tear strength 6.57 4.63 4.45
[0182] The results of the suture tear strength test and the tensile strength test were similar, indicating that the collagen matrix biomembrane with added gel-like collagen solution and subjected to gradient thermal cross-linking treatment has better mechanical strength.
[0183] ⑤ Wet volume stability test: Cut an appropriate amount of collagen matrix biomembrane and Mucograft product from Example 1, place them in physiological saline, and stir with a magnetic stirrer at 500 rpm for 3 minutes. Observe the degree of sample damage. The results are as follows: Figure 3 As shown, Figure a is a picture of the collagen matrix biofilm in Example 1 of this application after testing, and Figure b is a picture of the Mucograft product after testing.
[0184] The results showed that after being violently stirred and damaged by a magnetic stirrer, the collagen matrix biomembrane in Example 1 could still maintain its original shape, while the Mucograft product was obviously damaged and delaminated, and could not maintain its original shape, indicating that the collagen matrix biomembrane in this invention significantly improved volume stability.
[0185] The specific embodiments of this application have been described in detail above. For those skilled in the art, several improvements and modifications can be made to this application without departing from the principle of this application, and these improvements and modifications also fall within the protection scope of the claims of this application.
Claims
1. A method for preparing a collagen matrix biomembrane, characterized in that, include: S1: Prepare a decellularized matrix layer with a dense structure; S2: Preparation of collagen suspension; S3: After the collagen suspension is squeezed and injected into the mold to form, the decellularized matrix layer is moistened. The moistened decellularized matrix layer is spread evenly on the surface of the collagen suspension, the air bubbles are squeezed out, and it is left to stand so that the moistened decellularized matrix layer is tightly combined with the collagen suspension. S4: Freeze-dry the tightly bound decellularized matrix layer with the collagen suspension to obtain a composite freeze-dried layer; S5: The composite freeze-dried layer is subjected to gradient thermal cross-linking to obtain a collagen matrix biofilm; The collagen suspension is prepared from gel-like collagen solution and collagen fiber solution. 5-30 parts of gel-like collagen solution and 70-95 parts of collagen fiber solution are mixed, stirred evenly and defoamed under vacuum to obtain the collagen suspension. The preparation steps of the gel-like collagen solution include: S201 Decellularization: A decellularized matrix is prepared by pretreatment, virus inactivation, defatting, decellularization, and drying of animal tissues of natural origin; S202 pulverization: After the decellularized matrix is shredded, it is suspended in pure water to make the mass percentage of the decellularized matrix 0.5%-3.0%. The pH is adjusted to 3.0-4.0 with acid. The decellularized matrix is pulverized into a gel state using a tissue homogenizer to obtain a gel-like collagen solution. The preparation steps of the collagen fiber solution include: S211 Decellularization: A decellularized matrix is prepared by pretreatment, virus inactivation, defatting, decellularization, and drying of animal tissues of natural origin; S212 pulverization: The decellularized matrix is pulverized into irregular particles with a particle size of 0.2mm-2mm by low-temperature grinding and suspended in pure water to make the mass percentage of the decellularized matrix particles 0.5%-3.0%. The pH value is adjusted to 2.5-3.0 with acid to fully swell the decellularized matrix particles and obtain a decellularized matrix suspension. S213 Dehydration: Add sodium chloride powder to the decellularized matrix suspension until the sodium chloride concentration reaches 2.0-2.5 mol / L to obtain a white salting-out precipitate; wash the white salting-out precipitate with PBS buffer, centrifuge and concentrate to obtain collagen fibers; S214 dispersion: Collagen fibers are placed in an acidic solution with a pH of 3.0-4.0, so that the mass percentage of collagen fibers is 1%-6%. The collagen fibers are then mechanically stirred to form a uniform dispersion with slight swelling, thus obtaining a collagen fiber solution.
2. The method for preparing collagen matrix biomembrane according to claim 1, characterized in that: The decellularized matrix layer with a dense structure is a multi-layered composite decellularized matrix layer, wherein S1 further includes the following steps: S11 Decellularization: A decellularized matrix is prepared by pretreatment, virus inactivation, defatting, decellularization, and drying of animal tissues of natural origin; S12 composite: Vacuum pressing is used to composite 2-6 layers of decellularized matrix to obtain a multi-layer composite decellularized matrix layer.
3. The method for preparing collagen matrix biomembrane according to claim 1, characterized in that: The decellularized matrix layer with a dense structure is a recombinant decellularized matrix layer, wherein S1 further includes the following steps: S101 Decellularization: A decellularized matrix is prepared by pretreatment, virus inactivation, defatting, decellularization, and drying of animal tissues of natural origin; S102 pulverization: The decellularized matrix is pulverized into irregular particles with a particle size of 0.2mm-2mm by low-temperature grinding and suspended in pure water to make the mass percentage of the decellularized matrix particles 0.5%-3.0%. The pH value is adjusted to 2.5-3.0 with acid to fully swell the decellularized matrix particles and obtain a decellularized matrix suspension. S103 Dehydration: Add sodium chloride powder to the decellularized matrix suspension until the sodium chloride concentration reaches 2.0-2.5 mol / L to obtain a white salting-out precipitate; soak the white salting-out precipitate in an organic solvent for 0.5-2 hours to dehydrate, then wash with PBS buffer to remove the organic solvent and obtain collagen fibers; S104 Dispersion: Collagen fibers are suspended in PBS buffer to a collagen fiber mass percentage of 0.1%-6%, and a uniformly dispersed and fluffy collagen fiber suspension is obtained by mechanical stirring. S105 film formation: The collagen fiber suspension is passed through a vacuum filtration device to uniformly trap the collagen fibers on a filter membrane with a pore size of 0.8μm. Filtration continues until the collagen fibers are dry and semi-transparent. The recombinant decellularized matrix layer with a thickness of 0.1-0.5mm is obtained by peeling.
4. The method for preparing collagen matrix biomembrane according to claim 1, characterized in that: The naturally derived animal tissues include the submucosa of the small intestine of pigs or cattle, the peritoneum of pigs or cattle, the pericardium of pigs or cattle, the bladder of pigs or cattle, and the dermis of pigs or cattle.
5. The method for preparing collagen matrix biomembrane according to claim 3, characterized in that: The organic solvents include ethanol, acetone, diethyl ether, and isopropanol.
6. The method for preparing collagen matrix biomembrane according to claim 1, characterized in that: The wetting treatment of the decellularized matrix layer in step S3 is obtained by immersing the decellularized matrix layer in an acid with a pH of 3.0-4.0 for 10-30 minutes.
7. The method for preparing collagen matrix biomembrane according to any one of claims 3 or 6, characterized in that: The acids include hydrochloric acid, acetic acid, and citric acid.
8. The method for preparing collagen matrix biomembrane according to claim 1, characterized in that: The gradient thermal crosslinking in step S5 involves placing the composite freeze-dried layer in a vacuum chamber, evacuating it to less than -100 kPa, and maintaining it at 25℃-30℃ for 1-2 hours; then performing gradient temperature crosslinking by raising the temperature to 80℃-85℃ and holding it for 2-3 hours; continuing to raise the temperature to 100℃-105℃ and holding it for 2-3 hours; and finally raising the temperature to 120℃-125℃ and holding it for 24-48 hours.
9. A collagen matrix biomembrane, characterized in that: It is prepared by the preparation method described in claim 1.
10. An application of a collagen matrix biomembrane, characterized in that, include: The collagen matrix biomembrane prepared by the preparation method according to claim 1 can be used in the preparation of any one or more of the following materials: dental guided bone tissue regeneration material, dental soft tissue augmentation material, anti-tissue adhesion material, and chronic wound repair material.
Citation Information
Patent Citations
Collagen sponge
CN106999632B
Oral cavity repairing film and preparation method thereof
CN115006597A
Collagen matrix flap with stable wet volume and preparation method thereof
CN115501391A
Pig peritoneal acellular matrix sponge scaffold and preparation method thereof
CN116603106A
Collagen containing membranes for use in mucosa regeneration
EP1252903B1